Declino vs. permanenza: Intorno alla regia teatrale - Mazzocchi, Federica (Mimesis Journal, 2017)
Direction, with its transformations, aporias and persistences, is at the center of theatre studies. Which critical instruments and which methodologies can be used to deal with a paradigm characterized by such an unstable identity as the direction, often believed to be close to extinction, but always able to refound itself? Federica Mazzocchi’s essay moves from the reading of two contributions which approach the direction from completely different perspectives: Katie Mitchell, The Director’s Craft (2009) and Franco Cordelli, Declino del teatro di regia (2014). The aim is to bring into focus some of the methodological and historiographic problems which are looming today in the jagged territory of the direction.